Impacts of Fully Coupling Land Surface and Flood Models on the Simulation of Large Wetlands' Water Dynamics: The Case of the Inner Niger Delta - Augusto Getirana (American Geophysical Union (AGU), 2021)
Abstract It is known that representing wetland dynamics in land surface modeling improves models' capacity to reproduce fluxes and land surface boundary conditions for atmospheric modeling in general circulation models. This study presents the development of the full coupling between the Noah‐MP land surface model (LSM) and the Hydrological Modeling and Analysis Platform (HyMAP) flood model in the NASA Land Information System and its application over the Inner Niger Delta (IND), a well‐known hot‐spot of strong land surface‐atmosphere interactions in West Africa. Here, we define two experiments at 0.02° spatial resolution over 2002–2018 to quantify the impacts of the proposed developments on simulating IND dynamics. One represents the one‐way approach for simulating land surface and flooding processes (1‐WAY), that is, Noah‐MP neglects surface water availability, and the proposed two‐way coupling (2‐WAY), where Noah‐MP takes surface water availability into account in the vertical water and energy balance. Results show that accounting for two‐way interactions between Noah‐MP and HyMAP over IND improves simulations of all selected hydrological variables. Compared to 1‐WAY, evapotranspiration derived from 2‐WAY over flooding zones doubles, increased by 0.8 mm/day, resulting in an additional water loss rate of ∼18,900 km3/year, ∼40% drop of wetland extent during wet seasons, and major improvement in simulated water level variability at multiple locations. Significant soil moisture increase and surface temperature drop were also observed. Wetland outflows decreased by 35%, resulting in a substantial Nash‐Sutcliffe coefficient improvement, from −0.73 to 0.79. It is anticipated that future developments in water monitoring and water‐related disaster warning systems will considerably benefit from these findings.